Managing More-than-Moore Integration Technology Development A Story of an Advanced Technology Program in the Semiconductor Industry - Radojcic, Riko.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the real challenges and experiences of managing an advanced semiconductor technology development and integration program - but using a novelized form. The material is presented in a conversational format through a story that follows a fictional narrator as she grows from an intern to a manager in a (fictional) chip company. The story describes the technology development program from management, engineering and human perspectives, and exposes not only the management and technical issues but also the typical work-life balance challenges experienced by engineers working in the technology industry. Use of a series of realistic and representative vignettes, supported by a set of illustrative cartoon-ish panels, presents the serious management topics in a light and readable way. Based on real, hands-on experiences and presents actual lessons learned; Describes various aspects of managing an engineering development program; Explains key technical aspects of semiconductor technology to non-experts; Written in a novelized form that makes it very easy to read; Enables an understanding of how and why the chip industry evolved over the last 50 years into what it is today.
Section 1: I, Intern (& Setting up an Advanced Tech Integration Program) -- The Interview -- The Start -- The Background (and Beer with Cz) -- The Challenge (Why do Advanced Technology Development) -- The Value (of an Advanced Technology Program) -- The Knobs (for Setting Up an Advanced Technology Effort) -- The Proposals -- The Good-Bye -- A Technologist: Cz's Contemplations (circa year 0) -- Section 2: I, Engineer (& Running Integration Tech Development) -- I'm Back! -- Managing Learning (in a Matrix Organization) -- Managing Compensation (in a Matrix Organization) -- Reorganization (into Line Organization) -- The Challenge (How To Do the Integration Technology Development) -- Test Chip Engagement (& the Assignment I did not get) -- PathFinding Engagement (and the Assignment that I did get) -- A Manager: Steve's Soliloquy (circa + 3 years) -- Section 3: I, Leader (Product Intersection & Handing off the Learning) -- I'm Back! -- Process Transfer Case Study (IPD) -- Methodology Transfer Case Study (Multi-Physics Stress Modeling) -- Concept Transfer Case Study (2.5D Integration PathFinding) -- The Big Picture (Development of More-than-Moore Integration Technologies) -- A Businessman: Mao's Musings (Circa + 5 years).
Keywords: Electronic circuits; Technology -- Sociological aspects; Industrial Management; Electronic Circuits and Systems; Science, Technology and Society; Industrial Management